Efektifitas Edukasi Kesehatan Online Berbasis Zoom Cloud Meeting Terhadap Pengetahuan Manajemen Prehipertensi Pada Dewasa Prehipertensi - Tryastuti, Dini; Almubarok, Moh Fuad (Universitas Fort De Kock Bukittinggi, 2023)
Background: The implementation of new adaptations during the Covid 19 pandemic has led to an increase in the use of online applications as a means of Communication, Information and Education, one of them is the zoom cloud meeting application, this application is widely used in educational settings but is rarely used in implementing health education in the community, especially in increasing knowledes of the prehypertensive adult group.This study aims to identify the effectiveness of online health education in improving knowledge about how to manage prehypertension. Methods: The method used is a quasi-experimental with a control group of 70 respondents who were selected by purposive sampling. The intervention and control groups each amounted to 35 respondents. Health education online using zoom cloud meeting was given to the intervention group for ± 40 minutes (three times a week). Results: The results of this study indicated that there was an effect of online health education using zoom cloud meeting in improving knowledge about prehypertension management (p- value 0.001). Conclusion: In conclusion, online health education using zoom cloud meeting was effective in improving the knowledge about prehypertension management toward adults with prehypertension. Online health education using zoom cloud meeting can improve knowledge therefore it can be aplicated in community setting to improve knowledge about health management.Keywords: Online Health Education, Knowledge of Prehypertension Manajement, Zoom Cloud Meeting